Persistent hiccup as one of the initial symptoms of leucine-rich glioma-inactivated-1 encephalitis: a case report - Lan Hou; Li Wan; Hongshan Li; Zhehui Wang; Hongzhi Guan; Haitao Ren; Pei Wang (BMC Neurology, 2022)
Abstract Background Anti-leucine-rich glioma-inactivated 1 (LGI1) encephalitis, an autoimmune disorder, is characterized by faciobrachial dystonic seizures, epilepsy, memory deficits and altered mental status while hiccup is not commonly found in patients. Case presentation A 62-year-old male was presented with slurred speech, abnormal gait, faciobrachial dystonic seizures and impaired cognition. Besides, the hiccup was one of the initial symptoms. His brain magnetic resonance images (MRI) revealed multiple lesions with left caudate nucleus, putamen, insula and left hippocampus involvement. Because a diagnosis of antibody-related limbic encephalitis was suspected, studies including an autoimmune profile were done by cell-based assays. After anti-LGI1 antibodies were detected in both cerebrospinal fluid and serology, pulse methylprednisolone and intravenous immunoglobulin were started and hence hiccups disappeared along with other symptoms. Conclusions Clinicians should be aware that persistent hiccups might be one of the initial manifestations of LGI1 subtype of voltage-gated potassium channel complex antibody associated autoimmune encephalitis.